The Effect of the Guided Discovery Learning Model on Students' Creative Thinking Abilities in the Subject of 7th Grade Social Sciences, SMP Negeri 1 Peusangan - Asri Audi; Hariki Fitrah; Surya Darni (Journal Informatic, Education and Management (JIEM), 2026)
Creative thinking ability is a process of thinking imaginatively and originally in generating new ideas, formulating unusual solutions, and developing various alternative possibilities of a problem. This ability includes flexibility of thinking, fluency in generating ideas, elaboration, and originality. The low creative thinking ability of students is one of the challenges in the world of education today. One effort to improve creative thinking ability is to choose and apply the right learning model, which is able to stimulate students to think openly, explore ideas, and be active in a meaningful learning process. The purpose of this study was to determine the effect of the Guided Discovery Learning model on students' creative thinking ability in the Social Studies Subject of Class VII SMP Negeri 1 Peusangan. This study uses a quantitative approach. The type of research used is a quasi-experimental design. The sample in this study were students of class VII.4 taught using the Guided Discovery Learning learning model and referred to as the experimental class and class VII.5 taught without using a learning model or conventionally and referred to as the control class. Data collection techniques are observation, testing, and documentation. Based on the results of the hypothesis analysis, it shows that the Guided Discovery Learning learning model has a significant effect on students' creative thinking skills in class VII of SMP Negeri 1 Peusangan. This can be seen from the results of the significant test of the value obtained, the Sig <@ value is 0.000 <0.05. This means that Ha is accepted and Ho is rejected, which means that there is a significant influence between the use of the Guided Discovery Learning Model on students' creative thinking skills.